Stakeholder Relationship Model in Waste Bank Management in Madiun City - Fetria Widiyanti; Okid Parama Astirin; Evi Gravitiani (Jurnal Penelitian Pendidikan IPA, 2024)
In ‘Neraca Pengelolaan Sampah Kota Madiun‘ data for 2023, waste production was 44,750.39 tons/year, while the amount of waste reused and recycled was 4,600.28 tons/year and processed waste that went to landfill was 31,444.75 tons/year. Waste banks began to be formed in Madiun City from 2010 to 2023. There are 168 waste banks that have been formed and only 49.4% are still actively operating. The phenomenon found in the field is that involvement between stakeholders in the Waste Bank program in Madiun City is still not optimal, and this finding is the basis for this research, namely analyzing the relationship model of stakeholder roles in managing the Waste Bank in Madiun City. Madiun City. This research uses a mixed method paradigm to obtain a holistic picture of the characteristics and relationships of stakeholders in the Waste Bank program in Madiun City. All data in this study were analyzed using MACTOR software. The results of this research conclude that the stakeholders who have the greatest influence are DLH and public figure (Lurah) who are the main actors in waste bank management, because they are involved in planning, implementation and policy so that there is still a need to improve their relationships and roles in supporting the success of the waste bank program. Madiun City. Very strong convergence between actors shows that between the Matahari Sampah Bank and community leaders, Sedoro Asri Waste Bank, Sehati Waste Bank, Pesanggrahan Waste Bank and Risky Lancar Manis VI Waste Bank. Very weak convergence is shown between the Madiun City Environmental Service and NGOs, Pertamina, Academics, the PKK Mobilization Team and the Griya Kencana Waste Bank.